Advances at the procurement public during the Covid 19 in Colombia and Spain. - Montoya Castillo, Leyder; Rojas Calderón , Felipe; Malaver Rojas , Marleny Natalia (Scientific journal of social studies, 2022)
Due to the COVID-19 pandemic, international leaders through the administration acted in an atypical way due to the health emergency. Thanks to this situation, the contracting of a public health emergency was created in Colombia and Spain, with the aim of recovering the growth of the economy and containing the spread of the virus. Consequently, the regulation of the normative figure of the advance payment in Spain in the contracts entered into by public institutions were affected, , while in Colombia it was not changed, that is why this article was made by means of the qualitative-descriptive method, in which the substantial changes that the regulations suffered were identified, when generating these emergency contracts and how exceptions were established by the governments themselves as a result of the application of new legal regulations. Therefore, we intend to respond to the next question ¿What were the most important changes derived from the pandemic on the advance in Colombia and Spain and its relationship with corruption? According to the analysis carried out, cases of corruption in public contracting and advances are considered, it was determined that the mismanagement of the figure has triggered several relevant events where this phenomenon occurs, however it is not the absolute generator of the problem. Regarding the comparison, between the countries, it is identified that Colombia uses the advance with the highest proportion, contrary to what was established in Spain, even before the pandemic.